2014
DOI: 10.1111/cogs.12138
|View full text |Cite
|
Sign up to set email alerts
|

Judgments About Fact and Fiction by Children From Religious and Nonreligious Backgrounds

Abstract: In two studies, 5-and 6-year-old children were questioned about the status of the protagonist embedded in three different types of stories. In realistic stories that only included ordinary events, all children, irrespective of family background and schooling, claimed that the protagonist was a real person. In religious stories that included ordinarily impossible events brought about by divine intervention, claims about the status of the protagonist varied sharply with exposure to religion. Children who went to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
87
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(109 citation statements)
references
References 28 publications
17
87
3
2
Order By: Relevance
“…Regardless of whether described characters and events were actually possible or not, preschoolers judged events that were embedded in realistic stories as more likely to happen in real life than events embedded in fantastical stories. Corriveau, Chen, and Harris (2014) also examined the effect of realistic stories, religious stories, and fantastical stories on 5-and 6-year-olds' judgments of the reality status of the protagonist. They found that children were able to use realistic contexts to conclude that a character was real but differed on how they judged the protagonist in the religious and fantastical stories according to the children's exposure to religion; specifically, children with a religious upbringing were more likely to claim that religious events were real.…”
Section: -And 6-yearoldsmentioning
confidence: 99%
“…Regardless of whether described characters and events were actually possible or not, preschoolers judged events that were embedded in realistic stories as more likely to happen in real life than events embedded in fantastical stories. Corriveau, Chen, and Harris (2014) also examined the effect of realistic stories, religious stories, and fantastical stories on 5-and 6-year-olds' judgments of the reality status of the protagonist. They found that children were able to use realistic contexts to conclude that a character was real but differed on how they judged the protagonist in the religious and fantastical stories according to the children's exposure to religion; specifically, children with a religious upbringing were more likely to claim that religious events were real.…”
Section: -And 6-yearoldsmentioning
confidence: 99%
“…That is, they were likely to judge improbable events as impossible and did not show adult-like response patterns until age 8. In recent work by Corriveau, Chen, and Harris (2014), 5-and 6-year-old children were asked to make judgments about the reality status of protagonists in realistic, religious, and fantastical stories. Children from secular backgrounds were more likely than those from religious backgrounds to deny that the protagonist in religious stories was a real person.…”
Section: Children's Treatment Of Inconsistent Illogical and Improbamentioning
confidence: 99%
“…elicit less rejection and an interest in the kind of access that the speaker had when making the claim (Brosseau-Liard & Birch, 2011). Further, claims that are not internally inconsistent but that violate aspects of the child's experience and knowledge of the physical world (e.g., miraculous or impossible claims) invite different interpretations depending on the child's prior experience (Corriveau et al, 2014). While more work is needed, research investigating different types of "message conflicts" suggests that children are interested in the kind of backing or support that a claim receives and also, that what backing suffices depends upon the claim it is to meant to support.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…For example, after hearing stories about familiar biblical miracles (e.g., the parting of the Red Sea), religiously-raised 4- to 6-year-olds often judged that the protagonists were real people (Vaden & Woolley, 2011). By contrast, children with no exposure to religion via church attendance or school dismissed the protagonists as make believe and cited the impossibility of the miracle to justify their assessment (Corriveau, Chen, & Harris, in press). …”
Section: Believing Counterintuitive Claimsmentioning
confidence: 99%